The role of internal auditing in ensuring governance in Islamic financial institution (IFI) - Yahya, Y.; Mahzan, N.M. (2012)
Auditing in the Islamic framework has wider scope than the current practice of auditing due to the distinct worldviews and concepts (Hamid et.al., 1993; Haneef, 1997; Abdul Rahman, 2008) embedded in Islamic regulation known as ‘shariah’. The two main issues are related to the shariah audit framework and the factors affecting their judgment of internal auditors while conducting audit of Islamic financial institutions. Shariah audit might simply be defined as an audit attestation for shariah compliance. In Malaysia, Central Bank of Malaysia (BNM) issued a guideline on the Shariah Governance Framework (SGF) 2010, which has specified that shariah audit should be conducted by internal auditors However, little is known on what should be the practical model defining issues such as scope, extent, audit reporting, qualifications as well as current practices and understanding of shariah auditing in Islamic financial institutions. This study attempts to investigate current practice of shariah auditing among IFIs in Malaysia. Research data for this study is obtained from 5 semi structured interviews conducted with chief audit executive of IFIs. It is discovere that, the practices are still at development stage and need further improvement. For instance to increase the understanding of shariah auditing among internal auditors, enhance the shariah knowledge of internal auditors, standardization of shariah audit framework and providing general guidelines to design audit program for shariah auditing.